IMPLIKASI PENGELOLAAN SAMPAH RUMAH TANGGA MELALUI BANK SAMPAH TERHADAP KESEJAHTERAAN SOSIAL DAN EKONOMI DI DESA GALAGAMBA KECAMATAN CIWARINGIN KABUPATEN CIREBON - Fasya Amelia Siregar; Ferdhiyanto, Muhammad Annas; Irul Juliar Rahman (Faculty of Economics and Business Lampung University, 2025)
Waste is one of the problems that has not yet been resolved. Waste management must be carried out effectively and comprehensively, especially household waste management. The Waste Bank is an effort to overcome the increasing problem of household waste. The effectiveness of using the Waste Bank will later improve the social and economic welfare of the community in Galagamba Village. Through the Empirical Method with an analytical and observational approach, the aim is to study and encourage stakeholders and the community to realize effective waste management. Waste management is not yet effective and the quality of human resources must be improved. The suggestions given are to improve waste services, involve stakeholders, the community and the private sector, and strictly implement regulations related to waste.